2023
DOI: 10.1101/2023.02.03.526994
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An integrated map of cell type-specific gene expression in pancreatic islets

Abstract: Pancreatic islets are comprised of multiple endocrine cell types that produce hormones required for glucose homeostasis, and islet dysfunction is a major factor in the development of type 1 and type 2 diabetes (T1D, T2D). Numerous studies have generated gene expression profiles in individual islet cell types using single cell assays. However, there is no canonical reference of gene expression in islet cell types in both health and disease that is also easily accessible for researchers to access, query, and use… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(43 citation statements)
references
References 48 publications
5
26
0
Order By: Relevance
“…As shown in Figure 1B , our qPCR analysis revealed that Il33 expression in pancreatic pericytes was two orders of magnitude higher than in other analyzed cell populations. Similarly, IL33 expression in the human islets was restricted to the pericytic cell cluster ( Figure S1 ) ( 48 ).…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…As shown in Figure 1B , our qPCR analysis revealed that Il33 expression in pancreatic pericytes was two orders of magnitude higher than in other analyzed cell populations. Similarly, IL33 expression in the human islets was restricted to the pericytic cell cluster ( Figure S1 ) ( 48 ).…”
Section: Resultsmentioning
confidence: 92%
“…As shown in Figure 1A , mouse pancreatic pericytes express IL-33 but no other members of the IL-1 family of cytokines. To define IL33 expression in human islets, we employed a published islet cell transcriptome ( 48 ). Indeed, IL33 is expressed by pericytes, identified by the pericytic markers PDGFRB , ACTA2 , ENG , and CD248 ( 30 , 48 )( Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Gene expression signature scores were calculated using AddModuleScore function from Seurat package. To further confirm our cell annotations, first, we performed reference-based mapping using Azimuth R packages (version 0.4.6) 29 and employed previously annotated human islet cell dataset as reference 31 . Predicted cell annotation was projected on our integrated data UMAP with all cells, and the expression level of annotation markers used by Elgamal et al was visualized by DotPlot 31 .…”
Section: Methodsmentioning
confidence: 99%